Substituted cyclopentannulated tetraazapentacenes - Maier, Steffen; Heckershoff, Robin; Hippchen, Nikolai; Brödner, Kerstin; Rominger, Frank; Freudenberg, Jan; Hashmi, A. Stephen K.; Bunz, Uwe H. F. (Chemistry - a European journal, 2022)
Brominated pentannulated dihydrotetraazapentacenes were prepared by gold- or palladium-catalyzed 5-endo-dig cyclization of TIPS-ethynylated dihydrotetraazaacenes (TIPS = triisopropylsilyl). Post-functionalization was demonstrated by Sonogashira alkynylation and Rosenmund-von Braun cyanation. Calculations predict these species to act as n-type semiconductors, which was verified for two derivates through characterization in organic field-effect transistors.
Gesehen am 27.02.2023